Case Report: The Emerging Role of Ring Chromosome 22 in Phelan-McDermid Syndrome With Atypical Teratoid/Rhabdoid Tumor: The First Child Treated With Growth Hormone - Crocco, Marco; Panciroli, Marta; Milanaccio, Claudia; Morerio, Cristina; Verrico, Antonio; Garrè, Maria Luisa; Di Iorgi, Natascia; Capra, Valeria (Frontiers in Neurology, 2021)
Atypical teratoid/rhabdoid tumors (AT/RTs) in the rhabdoid tumor predisposition syndromes are most often caused by germline mutations of the SMARCB1 gene located in chromosome 22q11.2. Although rarely, it can also result from the constitutional ring chromosome 22 (r22): during mitosis the ring chromosome may lead to an increased rate of somatic mutations, resulting in rhabdoid tumor predispositions when the tumor-suppressor gene SMARCB1 is involved. Individuals with r22 may present similar features as those with Phelan-McDermid syndrome (PMDS) due to 22q13.3 deletion, including the SHANK3 gene. Despite several reports on AT/RT in children with r22 and/or PMDS have been published, the role of constitutional r22 as new oncogenic mechanism for AT/RT is still under investigation. There is not a lot of data available on therapeutic and prognostic implications of r22 in AT/RT and PMDS. Herein, we present the first case of a child with constitutional r22, PMDS and AT/RT of the brain, who is a long term survivor and is been treated with growth hormone. We also describe an unexpected adverse reaction to midazolam.